Analysis of Determinants of Poverty Levels in West Nusa Tenggara Province 2018-2023 - Hayuningrat, Andika Inggil; Wijimulawiani, Baiq Saripta; Wafik, Ahmad Zaenal (West Science Social and Humanities Studies, 2025)
This study aims to determine the effect of the human development index, economic growth, open unemployment rate, and gini ratio partially and simultaneously on poverty in West Nusa Tenggara Province. The method used is a quantitative method. The data analysis technique uses a panel data regression model. This study uses secondary data, namely a combination of 6-year time series data and a cross section of 10 districts/cities in West Nusa Tenggara Province. The results of this study indicate that the variables of the human development index, economic growth have a significant negative effect on poverty, while the open unemployment rate has a significant positive effect on poverty and the gini ratio has a negative insignificant effect on poverty in West Nusa Tenggara Province in 2018-2023.